2’-O-methoxyethyl splice-switching oligos correct splicing from IVS2-745 β-thalassemia patient cells restoring HbA production and chain rebalance - Alisa Dong; Valentina Ghiaccio; Irene Motta; Shuling Guo; Raechel Peralta; Susan M. Freier; Andy Watt; Sagar Damle; Yasuhiro Ikawa; Danuta Jarocha; Maxwell Chappell; Coralea Stephanou; et al. (Haematologica, 2021)
β-thalassemia is a disorder caused by altered hemoglobin protein synthesis and affects individuals worldwide. Severe forms of the disease, left untreated, can result in death before the age of 3 years (1). The standard of care consists of chronic and costly palliative treatment by blood transfusion combined with iron chelation. This dual approach suppresses anemia and reduces iron-related toxicities in patients. Allogeneic bone marrow transplant is an option, but limited by the availability of a highly compatible HSC donor. While gene therapy is been explored in several trials, its use is highly limited to developed regions with centers of excellence and well-established healthcare systems (2). Hence, there remains a tremendous unmet medical need to develop alternative treatment strategies for β-thalassemia (3). Occurrence of aberrant splicing is one of the processes that affects β-globin synthesis in β-thalassemia. The (C>G) IVS-2-745 is a splicing mutation within intron 2 of the β-globin gene. It leads to an aberrantly spliced mRNA that incorporates an intron fragment. This results in an in-frame premature termination codon that inhibits β-globin production. Here, we propose the use of uniform 2’-O-methoxyethyl (2’-MOE) splice switching oligos (SSOs) to reverse this aberrant splicing in the pre-mRNA. With these lead SSOs we show aberrant to wild type splice switching. This switching leads to an increase of adult hemoglobin (HbA) up to 80% in erythroid cells from patients with the IVS-2-745 mutation. Furthermore, we demonstrate a restoration of the balance between β-like- and α-globin chains, and up to an 87% reduction in toxic α-heme aggregates. While examining the potential benefit of 2’-MOE-SSOs in a mixed sickle-thalassemic phenotypic setting, we found reduced HbS synthesis and sickle cell formation due to HbA induction. In summary, 2’-MOE-SSOs are a promising therapy for forms of β-thalassemia caused by mutations leading to aberrant splicing.